The role of customer satisfaction in enhancing customer loyalty in Malaysian Islamic banks - Amin, Muslim; Isa, Zaidi; Fontaine, Rodrigue Ancelot Harvey (Routledge, Taylor and Francis Group, 2010)
This study examines the role of customer satisfaction in enhancing the loyalty of Muslim and non-Muslim customers in the Malaysian Islamic banking industry. Respondents are the customers (Muslim and non-Muslim customers) visiting the bank counters and have an account with Islamic banks. A total of 660 questionnaires were distributed, and 440 were returned. The results indicate that customer satisfaction has a statistically significant positive effect on customer loyalty and intentions to switch for Muslim and non-Muslim customers. However, there were significant differences in the effects of customer satisfaction on customer loyalty and intention to switch for Muslim and non-Muslim customers. The effect of customer satisfaction on customer loyalty and intention to switch is greater for the non-Muslim than the Muslim customers.